Marketing Communication Strategies in Increasing Brand Awareness: A Literature Review - Muh. Faisal Jufry (Pustaka Digital Indonesia, 2025)
In an increasingly competitive business landscape, companies must implement effective marketing communication strategies to strengthen brand awareness. Brand awareness plays a crucial role in shaping consumer perceptions, building trust, and influencing purchasing decisions. This literature review aims to analyze various marketing communication strategies that have proven successful in enhancing brand visibility across different industries. The study explores key strategies such as digital advertising, social media marketing, influencer marketing, content marketing, and data-driven approaches, examining their impact on consumer engagement and brand recognition. Additionally, this review discusses challenges companies face in executing these strategies, including evolving consumer behavior, regulatory constraints, and rapid technological advancements. By synthesizing findings from previous research, this paper provides valuable insights into the most effective marketing communication methods and their adaptability in different market conditions. Furthermore, it offers practical recommendations for businesses seeking to optimize their branding efforts in an increasingly digital environment. The study contributes to both academic literature and practical marketing applications by presenting a comprehensive framework for improving brand awareness. As businesses continue to navigate the dynamic marketing landscape, understanding and implementing strategic marketing communication approaches will be essential for long-term success and competitive advantage.